Social Isolation and the Use of Technology in Caregiving Dyads Living With Dementia During COVID-19 Restrictions - Hoel, Viktoria; Wolf-Ostermann, Karin; Ambugo, Eliva Atieno (Frontiers in Public Health, 2022)
Background People with dementia and their informal caregivers (caregiving dyads) face multiple impacts of the COVID-19 pandemic, including restricted social support services and social isolation. With limited opportunities for caregiving dyads to participate in social activities during the pandemic, the potential of social technology to support social participation and dyadic relationships should be explored. As a part of an ongoing feasibility trial, this study assesses how COVID-19 has impacted community-dwelling dyads in a dementia caregiving context. The dyads’ use of social technology and their motivations to invite technology into social interactions are explored. Methods A pilot case study employing baseline interview data from three community-dwelling caregiving dyads. Each dyad consisted of a husband with a dementia diagnosis and his wife, who performed most caregiving tasks. Interviews were audio-recorded, transcribed verbatim, and subjected to inductive thematic analysis. Two researchers independently coded the data, and collated the codes and themes collaboratively. Results Two themes and seven subthemes were identified: i) living with dementia during COVID-19 (subthemes: social and leisure activities, dyadic interactions, adjusting as caregiver); and ii) the role of technology in a pandemic (subthemes: facilitating social activities, facilitating dementia care-related activities, barriers and facilitators to using social technology, the underlying motivation to invite technology into interactions). Dyads who were socially active pre-COVID-19, and who managed to make good use of technology to facilitate and maintain their social engagement during COVID-19, reported to have been less negatively impacted by COVID-related social restrictions. Conclusion The dyads differed in how COVID-19 restrictions impacted their lives and how they coped with dementia, revealing different motivations for wanting to invite technology into their social interactions. During and beyond this pandemic, social technology can be a valuable tool for promoting social participation in this population, especially when in-person social contact is restricted. Successful uptake of social technology is dependent on customizing it to the individual’s needs and conditions. Therefore, efforts are needed to tackle barriers that exist for older adults in using such technology.